Resurrection and emended description of Reevesia lofouensis (Malvaceae) - Chen, Xin; Dong, Meng-Die; Deng, Hua-Ge; Li, Qiang (Phytotaxa, 2024)
Reevesia lofouensis (Malvaceae) from Guangdong, China, has been treated as a synonym of R. thyrsoidea recently. However, R. lofouensis differs from R. thyrsoidea in having densely yellowish stellate-tomentose branchlets and petioles, relatively large inflorescence with more flowers. Therefore, R. lofouensis is reinstated as a distinct species. An emended description of R. lofouensis with a detailed description of the flower is also provided here.